Studi Fenomenologi: Mengungkap Makna Akuntansi Pelanggan Dalam Perspektif UMKM Coffee Shop - Fernando, Steven; Angela, Nadya; Adrianto, Winny (Jurnal Akuntansi Publik Nusantara, 2023)
This study aims to examine the effect of customer accounting on the management strategies used by MSME coffee shops that are appropriate or not. Furthermore, analyzing which customers provide the most profitability to the MSME coffe shop business. The research that has been conducted uses a qualitative method, which comes from primary data whose data is taken from the results of interviews and observations at the MSME coffee shop. The results showed that customers who provide a lot of profit to MSME coffee shops in Pontianak City are teenagers or students, but besides that there are also many parents or families who provide benefits to MSME coffee shops in Pontianak City on certain days and hours. The results of this study, the handling of each MSME coffe shop has its own way to attract customers, for MSME coffe shops choose to hold events and discounts for customers, collaborate with third parties, adjust menu prices to suit customers, increase the variety of products to be sold according to the type of consumer so that consumers will be more consumptive, and add facilities in the form of free internet networks.